소아 탈장교정술 도중 생긴 방광 손상 - 고경훈(Kyoung Hoon Ko); 남소현(So Hyun Nam); 김대연(Dae Yeon Kim); 김성철(Seong Chul Kim); 김인구(In Koo Kim) (Annals of surgical treatment and research, 2006)
An inguinal hernia is common in pediatric age. However, an in injury to the bladder during hernia repair is quite rare, which may be related to the lack of awareness of the inguinal canal anatomy or inadequate exposure. Gross hematuria and voiding difficulty after herniorrhaphy may indicate a possible injury. Cystography can define the presence and type of injury. An extraperitoneal bladder injury can be managed safely by catheter drainage, antibiotics, and close clinical observations. An intraperitoneal injury requires surgical exploration and bladder closure. We report a case of a urinary bladder injury that was detected after the completion of herniorrhaphy in an eight-year-old girl. (J Korean Surg Soc 2006;71:315-318) KCI Citation Count: 0